Pathological changes caused by avian pathogenic Escherichia coliwith 4, 5 and 6 virulence associated genes in commercial broilers chickens - Zainal Abidin, Nurul Syuhada; Bejo, Mohd Hair; Zakaria, Zunita; Omar, Abdul Rahman; Bejo, Siti Khairani (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
Avian pathogenic Escherichia coli (APEC) strains were isolated from commercial broiler chickens in Johor and Melaka with clinical signs and gross lesions of E. coli infection. The isolates were molecularly characterized using multiplex PCR. APEC isolates with virulent associate genes (VAG) of 4 (Iss-irp2-iucD-vat and Iss-irp2-iucD-cva/cvi), 5 (Iss-irp2-papC-iucD-cva/cvi) and 6 (Iss-irp2-papC-iucD-vat-cva/cvi) were identified. More severe respiratory signs were recorded in chickens infected with APEC carrying papC gene when compared without the gene. The present of fibrinous lesions was associated with cva/cvi gene, an essential virulent trait of APEC. The vat gene which produces cytotoxic effect in the target cells was present in the VAG4 (dead chicken) and VAG6 groups, however in both groups the gross lesion were rather mild when compared to the other groups. The iss and iucD genes were present in all groups. Histological examination of all the organs was consistent with the findings on the gross lesions. It was concluded that the pathological changes observed in the chicken in the present study were closely associated with the present of the essential virulent genes of the APEC strains.